Pengaruh Gaya Kepemimpinan Terhadap Kinerja Karyawan Pada Perusahaan Tambang di Kalimantan Timur - Agsela Agsela; Pebriansyah Pebriansyah (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This study aims to analyze the influence of leadership style on employee performance at mining companies in East Kalimantan. Leadership style is one of the important factors that can influence employee motivation, discipline, and productivity in achieving organizational goals. This study uses a quantitative approach with a survey method. Data were obtained by distributing questionnaires to 100 respondents who were employees of several mining companies in the East Kalimantan region. Data analysis was conducted using simple linear regression to test the influence of the leadership style variable (X) on employee performance (Y). The results showed that leadership style has a positive and significant effect on employee performance. This means that the more effective the leadership style applied by the leader, the higher the level of employee performance. This finding indicates that leaders who are able to apply participatory and transformational leadership styles can increase employee morale and commitment to the company. This study is expected to be a reference for mining company management in developing effective leadership strategies to improve human resource performance